Two Formulations for non-Interference Parallel Machine Scheduling Problems. Issue 3 (2015) - Maschietto, Gabriela Naves; Ouazene, Yassine; Yalaoui, Farouk; de Souza, Maurício Cardoso; Ravetti, Martín Goméz
Abstract: This article deals with a job scheduling on two cranes subject to non-interference constraints. It is based on a real case at a distribution center of steel coils, where two cranes sharing the same rail must load a sequence of trucks, which has a defined demand of coils. The problem is mathematically modeled as a parallel machines with ordering variables and with time index variables. The proposed formulations are computationally tested among different instances. Based on the results, we discuss which formulation might work best for these problems.